The Medical School Curate: An Examination of Student Need - Schieffler, Danny A. (Journal of religion and health, 2011)
The intense and encompassing nature of medical education can be overwhelming at times. The impact that this effect has on a student can be mitigated if adequately trained, spiritually focused advisors are available and present within the campus setting. This article presents real case examples of, and recommendations for, the role of medical school chaplaincies and why those chaplaincies should be a part of the culture of medical education.